A biodegradable Fe/Zn–3Cu composite with requisite properties for orthopedic applications. (1st July 2022) - Tong, Xian; Zhu, Li; Wu, Yihao; Song, Yiting; Wang, Kun; Huang, Shengbin; Li, Yuncang; Ma, Jianfeng; Wen, Cuie; Lin, Jixing
Abstract: Zinc (Zn)-based metals and alloys are emerging as promising biodegradable implant materials due to their inherent biodegradability and good biocompatibility. However, this class of materials exhibits low mechanical strength and a slow degradation rate, which hinders their clinical application. Here we report the development of a new biodegradable Fe/Zn–3Cu composite fabricated by infiltration casting of a Zn–3Cu alloy into an Fe foam followed by hot-rolling. Our results indicate that the hot-rolled (HR) Fe/Zn–3Cu composite exhibited an α-Zn matrix phase, a secondary CuZn5 phase, and an α-Fe phase. The HR Fe/Zn–3Cu composite exhibited an ultimate tensile strength of 269 MPa, a tensile yield strength of 210 MPa, and an elongation of 27%. The HR Fe/Zn–3Cu composite showed a degradation rate of 228 µm/year after immersion in Hanks' solution for 30 d The diluted extract of the HR Fe/Zn–3Cu composite exhibited a higher cell viability than that of the HR Zn–3Cu alloy in relation to MC3T3-E1 and MG-63 cells. Furthermore, the HR Fe/Zn–3Cu composite showed significantly better antibacterial ability than that of the HR Zn–3Cu alloy in relation to S. aureus . Overall, the HR Fe/Zn–3Cu composite can be anticipated to be a promising biodegradable implant material for bone-fixation applications. Statement of significance: This work reports a new biodegradable Fe/Zn–3Cu composite fabricated by infiltration casting and followed by hot-rolling for biodegradable bone-fixation application. Our findings demonstrated that the hot-rolled (HR) Fe/Zn–3Cu composite exhibited an ultimate tensile strength of 269.1 MPa, a tensile yield strength of 210.3 MPa, and an elongation of 26.7%. HR Fe/Zn–3Cu composite showed a degradation rate of 227.6 µm/a, higher than HR Zn–3Cu alloy after immersion in Hanks' solution for 30 d The diluted extracts of the HR Fe/Zn–3Cu composite exhibited a higher cell viability than HR Zn–3Cu alloy toward MC3T3-E1 cells. Furthermore, the HR Fe/Zn–3Cu composite showed significantly better antibacterial ability than the HR Zn–3Cu alloy toward S. aureus . Graphical abstract: Image, graphical abstract